1995
DOI: 10.1523/jneurosci.15-09-05919.1995
|View full text |Cite
|
Sign up to set email alerts
|

Activity of the beta 3 nicotinic receptor promoter is a marker of neuron fate determination during retina development

Abstract: We have previously shown that transcription of the beta 3 nicotinic receptor gene within the chick CNS is regulated by a promoter 143 base pairs (bp) in length. Here, we demonstrate that in the developing visual system this promoter is active in a subset of retinal cells, the majority of which are ganglion cells. Because the beta 3 promoter is activated very early during retina development, it can provide a marker of ganglion cell induction and differentiation. Transfection of neuroretina explants enabled us t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
3

Year Published

1998
1998
2001
2001

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 36 publications
2
18
0
3
Order By: Relevance
“…The widespread expression of NeuroM and NeuroD in postmitotic cells at distinct times in neural development suggests that they do not define functionally distinct neuronal phenotypes but rather successive stages of a cell's life course (21,33). Transcription of the ␤3 gene is activated in a small subset of proliferating retinal cells, and then it is continuously expressed during cell differentiation and in the mature ganglion and amacrine cells (11). Although ASH-1, NeuroM, and NeuroD are expressed in subsets of retinal cells and instances of overlapping expression between these factors and ␤3 have been detected, we found that the ␤3 promoter was also active in cells that do not express these bHLH genes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The widespread expression of NeuroM and NeuroD in postmitotic cells at distinct times in neural development suggests that they do not define functionally distinct neuronal phenotypes but rather successive stages of a cell's life course (21,33). Transcription of the ␤3 gene is activated in a small subset of proliferating retinal cells, and then it is continuously expressed during cell differentiation and in the mature ganglion and amacrine cells (11). Although ASH-1, NeuroM, and NeuroD are expressed in subsets of retinal cells and instances of overlapping expression between these factors and ␤3 have been detected, we found that the ␤3 promoter was also active in cells that do not express these bHLH genes.…”
Section: Discussionmentioning
confidence: 99%
“…Chick embryos were staged according to Hamburger and Hamilton (25). Cells from different regions of the CNS were prepared as described previously (11,24). Neuroretina, pigment epithelium, optic tectum, telencephalon, and cerebellum were dissected from E4 -E13 embryos, collected in Ca 2ϩ -and Mg 2ϩ -free Hanks' balanced salt solution and incubated with 0.05% trypsin for 10 min (E4 -E8) or with 0.1% trypsin for 20 min (E9 -E13).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations